Persepsi Hukum Adat Larvul Ngabal Pada Masyarakat Kei Perantauan Di Kota Jayapura Provinsi Papua - Yusuf, Muhamad; Nofrita, Dewi; Mafiroh, Nanik Nikmal; Garamatan, Afan (POROS ONIM: Jurnal Sosial Keagamaan, 2021)
This study aims to find out about the understanding of the overseas Kei people in the city of Jayapura about the customary law of Larvul Ngabal and the impact of the values ​​of the customary law of Larvul Ngabal which are starting to disappear on the overseas Kei people in the city of Jayapura. Using qualitative methods with a social phenomenology paradigm. Research results: The phenomenon that occurs in the overseas Kei community in Jayapura city has experienced a degradation of its original culture, namely the Kei culture, where many of the Kei young generation, especially those who grew up in Jayapura City and who are mixed Kei people (one of their parents is not Kei), cannot speak Kei, this results in an inability to master the customary law of Larvul Ngabal, as well as the younger generation who can speak the Kei area (Veveu Evav) unable to master the contents of the law.  On the other hand, there is a strengthening of religious elements so that it erodes the existence of Larvul Ngabal customary law which without realizing that this customary law can unite various religions in the Kei community. The fundamental conflict is only related to the sanctions imposed by customary law which are still very burdensome for the Kei people, there is also an opinion that if the Kei culture is carried out in overseas areas, the use of caste in custom must be reopened.